Manajemen Sarana dan Prasarana untuk Mengembangkan Mutu Pendidikan di SMP Nurul Yaqin Pardasuka Pringswu - Latifa, Latifa; Gusliana, Evi; Ngarifin, Syeh Al; Mubarok, Ahmad (LPPPI Publishing, 2024)
The effectiveness of educational programs in schools is significantly affected by the condition of educational facilities also infrastructure. Dealing with infrastructure needs involves outlining also examining the processes related to planning, organizing, mobilizing, monitoring, supporting, as well as identifying factors that hinder infrastructure management to improve educational quality at SMP Nurul Yaqin. Qualitative research methods were employed for data gathering, which included observation, interviews, documentation, also triangulation. Data analysis consisted of collecting, reducing, presenting, also deriving conclusions. The findings of the study highlighted planning strategies such as annual meetings, program evaluation, work program reviews, program activity implementation, also parental program socialization. Elements of organization included considerations of organizational structure, staffing, job descriptions, responsibilities, communication, also coordination. Mobilization efforts covered procurement, inventory management, maintenance, selection, also reporting. Supervision entailed evaluation, oversight, also follow-up actions. Factors that supported the endeavor included effective design, staff placement, organized record-keeping, also the involvement of school supervisors. Conversely, inhibiting factors comprised the level of commitment of human resources, financial limitations, complex regulations, also inadequate opportunities for employee skill development.